Planning and Implementation of Event Marketing in Sociopreneurship - Evanthi, Ayundha; Mukti Azhar, Ratih (Publisher Cv. Inara, 2023)
Growing in popularity and garnering a lot of public attention right now is social entrepreneurship, which has the ability to lessen societal problems and enhance people's quality of life. Social entrepreneurs can utilize event marketing to enhance event experiences and boost behavioral intention. The purpose of this study is to outline the components of implementation, restrictions, and planning. Using participant observation approach methodologies, interviewing techniques, descriptive qualitative kinds, and source triangulation as a measure of data validity, this study examines the marketing of CIS (Creative Inclusion Sociopreneurship) events. The study's findings demonstrate how social entrepreneurship-focused events improve guests' event experiences through event marketing, where customers engage with brands and provide value. Events give customers the ability to directly engage with brand reality. Consumers help create the experience, thus through event marketing, the business should give them access to an engaging environment where experiences can occur. Event marketing is not only an idea; it needs to be put into practice. This study also indicates that intention and implementation are related, with the event influencing the intention to suggest and revisit the event as well as the desire to feel satisfied with the experience. The organizer of the sociopreneurship marketing event must assemble comprehensive planning and implementation recording that is clear, comprehensive, and includes all necessary information for pre-, main-, and post-event marketing.